Wear Resistance of Fe-based Nanostructured Hardfacing - Gualco, Agustín (2015)
The purpose of this work was to study the microstructural evolution and wear resistance of a nanostructured iron-based alloydeposited by FCAW process. Two samples with one and two layers were welded under Ar-20CO2 shielding and heat input of 3.5kJ/mm. Chemical composition was determined and microstructure was studied using both optical and scanning electronmicroscopy and X ray diffraction. Hardness, cristallite size, percentage of dilution and abrasive wear resistance were measured.The hardness of the deposit was found between 800 and 920 HV2, depending on the number of layers as well as the chemicalcomposition of the samples. The wear test results were discussed in relation to chemical composition, microstructure andhardness.